The Impact of Corona Outbreak on Virtual Education Policy in Iranian Universities - Yousef Amiri; Nima Khademi; Fatemeh Zare Khafri; Zahra Akbari; Roghayeh Jangjoo (Journal of Social, Humanity, and Education, 2022)
Purpose: The main purpose of this study is to the effect of the coronavirus outbreak on e-learning policy in Iranian universities. Research methodology: This research is a combined type and includes a section that has practical writing. In order to collect information in the first part, the method of library studies and theoretical analysis has been used. The second part of this study was controlled. Results: Systematic review of research conducted in the field of research variables showed that appropriate policy-making in education, especially virtual education, leads to a constructive change in the educational system that will lead to lifelong and applied education and learning.Individual and social note. In the quantitative part, data analysis was performed using spss25 software. The results of the analysis of 4 hypotheses in the study showed that the prevalence of the coronavirus has a significant effect on the e-learning policy in Iranian universities. Limitations: Lack of availability of research samples during the corona. Contribution: Ensuring educational policy with proper mechanisms and accountability after the Coronavirus period is one of the most important factors that play a major role in improving and effectiveness of virtual education.